Laboratory Flash Flotation Trends for a Variety of Gold Particles - McGrath, T; Eksteen, Jacques; Vaughan, Jeffrey Patrick; Heath, J (The Australian Institute of Mining & Metallurgy, 2013)
A reliable laboratory method to characterise the response of free gold particles when subjected to flash flotation conditions has been developed by AMIRA P420 researchers at Curtin University. This test has been applied to assess the flotation recovery of gravity recoverable gold from free milling ores as well as synthetic ores featuring either a gravity concentrate or gold powder. Trends in free gold flotation kinetics as well as size and milling effects were identified for gold recovery, based on the different gold types, reagent dosage and residence time.